Respuestas

2012-09-05T01:09:18+02:00

(2x)^2+(2y)^2-4x-12y-6=0\\ (2x)^2+(2y)^2-2*2*1x-2*2*3y+1+9-1-9-6=0\\ (2x)^2+(2y)^2-2*2*1x-2*2*3y+1+9=1+9+6\\ ((2x)^2-2*2*1x+1)+((2y)^2-2*2*3y+9)=16\\ (2x-1)^2\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ +(2y-3)^2 \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ =4^2\\ (2x-1)^2+(2y-3)^2=4^2\\

Dividimos\ entre\ 2^2 \ a\ ambos\ lados\ de\ la\ ecuacion\\ \\ \frac{(2x-1)^2+(2y-3)^2}{2^2}=\frac{4^2}{2^2}\\ \\ \frac{(2x-1)^2}{2^2}+\frac{(2y-3)^2}{2^2}=\frac{4^2}{2^2}\\ \\ (\frac{2x-1}{2})^2+(\frac{2y-3}{2})^2=(\frac{4}{2})^2\\ \\ (\frac{2x}{2}-\frac{1}{2})^2+(\frac{2y}{2}-\frac{3}{2})^2=(2)^2\\ \\ (x-\frac{1}{2})^2+(y-\frac{3}{2})^2=(2)^2\\ \\

 

Con esto sabemos que la circunferencia esta centrada en:

P=(1/2, 3/2)

r=2